IMPLEMENTASI NILAI BELA NEGARA TERHADAP SIKAP DISIPLIN SDM DI SDN SUMBERBENDO II - Zuhro, Warda Akhadatus; Abellita, Isal; Putri, Luthfiana; Nurmaulidya, Salsabila; Priambodo, Bayu (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research explores the implementation of the value of defending the country and its impact on disciplinary attitudes among society. Through this research, we explore individual views and experiences related to the values of defending the country as applied in everyday life. The results indicate that the implementation of national defense values positively contributes to the formation of a disciplinary attitude. An in-depth analysis of the interaction between national defense values and disciplinary attitudes provides new insights into how these values can be the main driver of behavior change. The aim of this research is to be used as a basis for developing educational strategies and social campaigns to increase public awareness of the importance of the value of defending the country in forming a strong disciplinary attitude. This type of research uses a qualitative descriptive method. This research data collection uses primary data and secondary data. First, primary data using questionnaires, observations and interviews. Second, secondary data using social environmental conditions and the government area that is the research location. The results of this research analysis were explained by the author using Bambang Sunggono's implementation theory, namely a theory that has four points (Policy, Process, Results, Impact). The conclusion from this analysis is that activities will experience obstacles, as happened at SDN Sumberbendo II, there are many obstacles faced, one of which is that many students do not use the attributes correctly, resulting in the discipline attitude of SDN Sumberbendo II students still not being optimal, however This does not prevent teaching staff from guiding their students.